# Thread: Solving for y

1. ## Solving for y

How is y solved for in this equation?

$x=\frac{1-\sqrt{y}}{1+\sqrt{y}}$

2. Multiply both sides of the equation by $1/(1 + \sqrt{y})$, then isolate $\sqrt{y}$. The rest will follow.

3. Did you make a typo in that formula?

4. Yes, should be multiplying both sides by $(1 + \sqrt{y})$

5. $x=\frac{1-\sqrt{y}}{1+\sqrt{y}}$
synthetically divide:
$x = \frac{2}{\sqrt{y}+1} - 1$
$x + 1= \frac{2}{\sqrt{y}+1}$
multiply by that denominator and divide by x+1:
$\sqrt{y} + 1 = \frac{2}{x + 1}$
subtract 1:
$\sqrt{y} = \frac{2}{x + 1} - 1$
find common denominator and add:
$\sqrt{y} = \frac{-x + 1}{x+1}$
square both sides:
$y = \frac{(-x+1)^2}{(x+1)^2}$
factor out -1 from numerator:
$y = \frac{(-[x-1])^2}{(x+1)^2}$
distribute ^2:
$y = (-1)^2\frac{(x-1)^2}{(x+1)^2}$
-1*-1 = 1:
$y = \frac{(x-1)^2}{(x+1)^2}$

6. Originally Posted by Mike9182
$x=\frac{1-\sqrt{y}}{1+\sqrt{y}}$
Another way:

x(1 + SQRT[y]) = 1 - SQRT[y]

x + xSQRT[y] = 1 - SQRT[y]

xSQRT[y] + SQRT[y] = 1 - x

SQRT[y](x + 1) = -1(x - 1)

SQRT[y] / -1 = (x - 1) / (x + 1)

y = [(x - 1) / (x + 1)]^2

7. Hello : 1005 and wilmer
you have one solution
but (1-x)/(1+x)>= 0

8. Originally Posted by dhiab
Hello : 1005 and wilmer
you have one solution
but (1-x)/(1+x)>= 0
Hmmm....isn't all that's required: x <> -1 ?